2002
DOI: 10.1038/sj.bjc.6600251
|View full text |Cite
|
Sign up to set email alerts
|

Autologous cell vaccine as a post operative adjuvant treatment for high-risk melanoma patients (AJCC stages III and IV)

Abstract: This study evaluates the overall survival and disease free survival of melanoma patients that were treated with an autologous melanoma cell vaccine, administered as a post-operative adjuvant. Included are 43 patients with totally resected metastatic melanoma (28-AJCC stage III, 15-AJCC stage IV), with a median follow up of 34 months (6 -62). The treatment consisted of eight doses of a vaccine made of 10 -25610 6 autologous melanoma cells either released from the surgical specimen or grown in cell cultures. Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…None of the patients who failed to demonstrate a positive DTH response had any objective tumour regressions, even with the addition of IL-2. In a previous study, we found a significant correlation between the development of strong positive DTH and (Lotem et al, 2002). Similar findings were reported by Berd et al (1990Berd et al ( , 2001 and Baars et al (2000).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…None of the patients who failed to demonstrate a positive DTH response had any objective tumour regressions, even with the addition of IL-2. In a previous study, we found a significant correlation between the development of strong positive DTH and (Lotem et al, 2002). Similar findings were reported by Berd et al (1990Berd et al ( , 2001 and Baars et al (2000).…”
Section: Discussionsupporting
confidence: 76%
“…They developed, however, recurrence in the midst of the adjuvant protocol (between vaccines 4 and 8; three patients) or within 2 years from its initiation (four patients). These seven patients were described elsewhere before (Lotem et al, 2002). They are included in the present series because they continued vaccination in the presence of active metastatic disease or were referred for successive IL-2 therapy.…”
Section: Treatment Framework (Figure 1)mentioning
confidence: 99%
“…All patients gave their informed consent to be included in the vaccination studies. The melanoma cell lines were established as described (15). To assure melanocytic progeny, the expression of S100, MART-1, and gp100 were evaluated by immunostaining using polyclonal rabbit anti-S100, monoclonal A-103, and HMB-45 antibodies, respectively (Dako).…”
Section: Methodsmentioning
confidence: 99%
“…Before vaccination, an appropriate amount of Bacillus Calmette-Guerin was added, starting with a dilution of 1:50 and reaching 1:500, according to the resulting granuloma at the injection site. The vaccination procedure was carried out as described (15,17). On day 1, patients received 300 mg/m 2 of i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Following incubation for 1 to 5 h at 37jC, cells were washed twice in PBS containing 0.5 mmol/L EDTA, to ensure conjugate dissociation, resuspended in PBS supplemented with 0.5% bovine serum albumin and 0.1% sodium azide, and stained with FITC-conjugated or PE-Cy5-conjugated or APC-conjugated anti-human CD8 and/or CD4 (eBioscience), CD107a (BD PharMingen), or isotype control mAbs. For specific TCR staining, cells were incubated with FITC-conjugated HLA-A*0201-MART-1 [26][27][28][29][30][31][32][33][34][35] or HLA-A*0201-gp100 154-162 dextramers (Dako) for 30 min at 4jC. The samples were washed and analyzed by FACScan and ''FCS Express'' software (De Novo).…”
Section: Methodsmentioning
confidence: 99%